Increase of lipids during HCV treatment: Virus action or medication? - De Andrade, Vanessa Gutierrez [UNESP]; Yamashiro, Fabio da Silva [UNESP]; Oliveira, Cassio Vieira [UNESP]; Kurozawa, Leticia Lastória [UNESP]; Moreira, Alecsandro [UNESP]; Silva, Giovanni Faria [UNESP] (FapUNIFESP (SciELO), 2018)
Background - The interaction between serum lipids and C virus infection is well known, as are serum lipid levels in the Peg-IFN/RBV-based treatment. However, with direct action antivirals (DAAs) this behavior is still unclear. Objective - To compare serum lipids levels between patients treated with Peg-IFN/RBV and DAAs and to evaluate lipids in sustained virological response (SVR) with DAAs. Methods - Retro prospective study comparing the behavior of total cholesterol (TC), low-density lipoprotein (LDL) and triglycerides (TG) serum levels during treatment with DAAs (G-DAAs) and a control historic group Peg-IFN/RBV (G-PR). Coorte, prospective study, to study the behavior of lipids in the SVR with DAAs. Data were collected at the beginning of treatment (baseline: t-base) and at week 12 of treatment (t-12) for G-DAAs and at week 24 (t-24) for G-PR, groups. In the cohort evaluation, the samples at t-base and at week 12 after the end of treatment (t-SVR). Delta lipids: difference between lipids in t-12/t-24 minus t-base for comparison between G-PR and G-AADs groups and t-SVR minus t-base for lipid analysis in SVR. Analysis with Kruskal Wallis and Wilcoxon tests to compare the delta lipids of the groups. The P value was 0.05. Results - In the assessment between G-PR and G-DAAs groups, we included 63 and 121 patients, respectively. The groups did not differ one from the other (BMI, sex, genotype, fibrosis, total cholesterol, LDL, and TG) except by age (50.38 ± 10.44 vs 56 ± 9.69, P=0.0006). We observed a decrease in levels of TC and LDL and an increase in TG, in G-PR, and in G-DAAs the opposite (Δ TC -13.9 ± 34.5 vs 4.12 ± 34.3 P=0.0005, Δ LDL -7.16 ± 32 vs 10.13 ± 29.92, P=0.003, Δ TG 4.51 ± 53.7 vs -8.24 ± 49.93, P=0.0025). In the coorte analysis, we included 102 patients, 70% men and 56% F4, 95 of them reached SVR. We observed an increase of TC and LDL and a decrease of TG in both groups (SVR and non SVR), with no statistical difference (Δ TC P=0.68; Δ LDL P=0.69; Δ TG P=0.43). We did not find significant difference in delta evaluation by genotype 1 and 3 (Δ TC +29.7 ± 40.2 vs +13.4 ± 30.3, P=0.06; Δ LDL +21.4 ± 28.6 vs +16.6 ± 31.3, P=0.41; Δ TG -3.6 ± 60.6 vs -0.7 ± 40, P=0.91). Conclusion - Serum lipids level differed during treatment with Peg-IFN and DAAs. Treatment with DAAs was associated with an increase of TC and LDL and a decrease of TG, independently of SVR.
Aumento dos lipídes durante tratamento para VHC: Ação do vírus ou da medicação?
Keywords: Antiviral agents; Hepatitis C; Interferon-alpha; Lipid metabolism; Therapeutic use; Virological analysis